An IoT-based Smart Doorbell System for Mitigating Stealth Attacks - Osifeko, Martins; Iroegbu, Godswill; Okubanjo, Ayodeji (Journal of Engineering Science, 2024)
The need for smart doorbell systems has increased in recent times. This is due to the general tendency for burglars to use stealth when breaking into homes and businesses. Also, visitors are known to spend time searching for doorbells around the house. Thus, to address this problem, this paper presents a smart doorbell system that detects human presence at the door and automatically notifies the homeowner. The system consists of a microcontroller, ultrasonic sensor, GSM module, and software. When a human presence is detected within the configured range of 1 to 70cm, the ultrasonic sensor sends a signal to the microcontroller, which in turn sends a command to the GSM module to notify the homeowner. The performance of the system was tested using various parameters with results showing that the device can detect human presence within the range of 1-80cm. Journal of Engineering Science 14(2), 2023, 47-58